Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations ANNUAL SUBSCRIBERS, 1932. £ s. d. Alford, A. G., Esq. 1 1 0 Andrew, Mrs. 1 1 0 Andrew, Mrs. H. 1 1 0 Ashford, Miss 10 0 Austin, Miss 2 6 Bard, Cecil, Esq. 10 0 Bishop, The late Mrs. 10 0 Bristow, F. E., Esq. 10 0 Brock & Co., Messrs. (1931-32) 1 1 0 Brock, The Misses 1 1 0 Browne, Mrs. Scott 2 0 0 Browne, Mrs. Walter 2 2 0 Buller, Major, M. L., M.C. 1 0 0 Chattock, Mr. and Mrs. 2 2 0 Chudley, Mrs. R. D. 2 2 0 Clarke, R. S., Esq. 1 1 0 Clarke, F., Esq. 1 1 0 Courtier, Mrs. 1 1 0 Custance, Mrs. 1 1 0 Cutcliffe, Miss 1 1 0 Dent, Mrs. 3 3 0 Depree, Mrs. 1 1 0 Devon Trading Co. 10 0 Dodd, Dr. 1 1 0 Dunsford, M. J., Esq. 5 0 Dyball, B., Esq., F.R.C.S. 5 5 0 Dyke Acland, Col. 5 5 0 Ellett Lake, J., Esq. (1931-32) 2 2 0 Ellis, Mrs. 10 0 Girls' Diocesan Association 25 0 0 Glanfield, T., Esq. 1 1 0 Hall, Mrs. (1931-32) 2 2 0 Hardinge, Mrs. 1 0 0 Harding, Mrs. 1 1 0 Hare, Mrs. 2 2 0 Hepburn, Miss 2 2 0 Hunter, F. C., Esq. 5 5 0 Hutchinson, Mrs. K. E. 1 1 0 Hutchinson, Mrs. W. E. 1 1 0 Jeboult, Messrs. A. H. 5 0 Lear, Brown & Dunsford, Messrs. 1 0 0 Lloyd, Miss K. A. 2 2 0 Lloyd, Miss 1 1 0 Liddell, Lt.-Col. 1 1 0 Mamhead, Lord (1931-32) 2 0 0 Mardon, E. J., Esq. 1 1 0 Marston, Mrs. 10 6 Mathew, Miss 5 0 May, Lady, M.B.E. 1 1 0 May, Major-Gen. Sir E. 1 1 0 McLaren, Canon 5 0 Melhuish, Mrs. T. W. W. 1 1 0 54 292/841.51/2/2